In vitro and in vivo anti−Toxoplasma activities of HDAC inhibitor Panobinostat on experimental acute ocular toxoplasmosis - Zhang, Yu; Zhang, Qingqing; Li, Haiming; Cong, Hua; Qu, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
Ocular toxoplasmosis (OT) is retinochoroiditis caused by Toxoplasma gondii infection, which poses a huge threat to vision. However, most traditional oral drugs for this disease have multiple side effects and have difficulty crossing the blood-retinal barrier, thus the new alternative strategy is required to be developed urgently. Histone deacetylases (HDAC) inhibitors, initially applied to cancer, have attracted considerable attention as potential anti-Toxoplasma drugs. Here, the efficacy of a novel HDAC inhibitor, Panobinostat (LBH589), against T. gondii were investigated. In vitro, LBH589 inhibited the proliferation and activity of T. gondii in a dose-dependent manner with low toxicity to retinal pigment epithelial (RPE) cells. In vivo, optical coherence tomography (OCT) examination and histopathological studies showed that the inflammatory cell infiltration and the damage to retinal architecture were drastically reduced in C57BL/6 mice upon treatment with LBH589. Furthermore, we found the mRNA expression levels of inflammatory cytokines were significantly decreased in LBH589–treated group. Collectively, our study demonstrates that LBH589 holds great promise as a preclinical candidate for control and cure of ocular toxoplasmosis.